Aktywność fizyczna a choroby cywilizacyjne osób starszych = Physical activity and older people's civilization diseases - Magdalena Kotlarek; Mirosława Szark-Eckardt; Pavol Bartik; Walery Zukow (Kazimierz Wielki University, 2015)
Kotlarek Magdalena, Szark-Eckardt Mirosława, Bartik Pavol, Zukow Walery. Aktywność fizyczna a choroby cywilizacyjne osób starszych = Physical activity and older people's civilization diseases. Journal of Education, Health and Sport. 2015;5(9):397-412. ISSN 2391-8306. DOI10.5281/zenodo.31000 http://dx.doi.org/10.5281/zenodo.31000 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A397-412 https://pbn.nauka.gov.pl/works/626190 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 13.09.2015. AKTYWNOŚĆ FIZYCZNA A CHOROBY CYWILIZACYJNE OSÓB STARSZYCH Physical activity and older people's civilization diseases   Kotlarek Magdalena1, Szark-Eckardt Mirosława1, Bartik Pavol1, Zukow Walery1   1Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Instytut Kultury Fizycznej   Streszczenie Aktywność fizyczna wpływa pozytywnie na zdrowie każdego człowieka. Ruch nie tylko zapobiega, ale także jest sposobem na leczenie wielu chorób cywilizacyjnych. Celem pracy było zbadanie świadomości osób starszych w zakresie aktywności fizycznej, tego w jakim stopniu mają z nią do czynienia i czy ma ona wpływ na radzenie sobie z chorobami cywilizacyjnymi, jakie najczęściej dotykają osoby starsze, takie jak: nadciśnienie tętnicze, cukrzyca czy miażdżyca. Aktywność fizyczna to nie tylko dyscypliny sportu, ale także prozaiczne porządki w ogrodzie czy też piesze wyjście na zakupy. Największą popularnością cieszą się wśród badanych takie formy aktywności jak: spacer, nordic walking i jazda rowerem. Wywnioskować można, że formy te wybierane są m.in. ze względu na mały wkład finansowy oraz niewielki stopień trudności. Większość badanych podejmuje ruch dla przyjemności i rozrywki, łącząc aktywność fizyczną z pożytecznym sposobem na spędzanie wolnego czasu. Aktywność fizyczna połączona z odpowiednią dietą stanowi nieodłączny element pomyślnej starości oraz jakości życia.   Słowa kluczowe: ruch, choroby, zdrowie, okres starości, aktywność fizyczna.       Abstract               Physical activity contributes to the health of every human being. Not only prevents movement, but also is a way to treat many of the diseases of civilization.             The aim of the study was to investigate the awareness of older people in terms of physical activity, the extent to which they have to deal with it, and whether it has an impact on coping with diseases connected with civilization, which most commonly affect the elderly, such as hypertension, diabetes or atherosclerosis.             Physical activity is not only sport, but also mundane chores in the garden, or walking out. The most popular among the surveyed such activities as walking, nordic walking and cycling. You can deduce that these forms are selected. because of the small financial contributions and a small degree of difficulty. The majority of interviewees take the movement for pleasure and entertainment, combining physical activity with a useful way of spending free time.             Physical activity combined with a proper diet is an inherent element of the successful old age and quality of life.   Keywords: motion, sickness, health, old age, physical activity.